Survival outcomes and independent response assessment with nivolumab plus ipilimumab versus sunitinib in patients with advanced renal cell carcinoma: 42-month follow-up of a randomized phase 3 clinical trial. Issue 2 (12th July 2020) - Motzer, Robert J; Escudier, Bernard; McDermott, David F; Arén Frontera, Osvaldo; Melichar, Bohuslav; Powles, Thomas; Donskov, Frede; Plimack, Elizabeth R; Barthélémy, Philippe; Hammers, Hans J; George, Saby; Grünwald, Viktor; et al.
Abstract : Background: The extent to which response and survival benefits with immunotherapy-based regimens persist informs optimal first-line treatment options. We provide long-term follow-up in patients with advanced renal cell carcinoma (aRCC) receiving first-line nivolumab plus ipilimumab (NIVO+IPI) versus sunitinib (SUN) in the phase 3 CheckMate 214 trial. Survival, response, and safety outcomes with NIVO+IPI versus SUN were assessed after a minimum of 42 months of follow-up. Methods: Patients with aRCC were enrolled from October 16, 2014, through February 23, 2016. Patients stratified by International Metastatic Renal Cell Carcinoma Database Consortium (IMDC) risk and region were randomized to nivolumab (3 mg/kg) plus ipilimumab (1 mg/kg) every 3 weeks for four doses, followed by nivolumab (3 mg/kg) every 2 weeks; or SUN (50 mg) once per day for 4 weeks (6-week cycle). Primary endpoints: overall survival (OS), progression-free survival (PFS), and objective response rate (ORR) per independent radiology review committee in IMDC intermediate-risk/poor-risk patients. Secondary endpoints: OS, PFS, and ORR in the intention-to-treat (ITT) population and safety. Favorable-risk patient outcomes were exploratory. Results: Among ITT patients, 550 were randomized to NIVO+IPI (425 intermediate/poor risk; 125 favorable risk) and 546 to SUN (422 intermediate/poor risk; 124 favorable risk). Among intermediate-risk/poor-risk patients, OS (HR, 0.66; 95% CI, 0.55–0.80) and PFS (HR, 0.75; 95% CI, 0.62–0.90) benefits were observed, and ORR was higher (42.1% vs 26.3%) with NIVO+IPI versus SUN. In ITT patients, both OS benefits (HR, 0.72; 95% CI, 0.61–0.86) and higher ORR (39.1% vs 32.6%) were observed with NIVO+IPI versus SUN. In favorable-risk patients, HR for death was 1.19 (95% CI, 0.77–1.85) and ORR was 28.8% with NIVO+IPI versus 54.0% with SUN. Duration of response was longer (HR, 0.46–0.54), and more patients achieved complete response (10.1%–12.8% vs 1.4%–5.6%) with NIVO+IPI versus SUN regardless of risk group. The incidence of treatment-related adverse events was consistent with previous reports. Conclusions: NIVO+IPI led to improved efficacy outcomes versus SUN in both intermediate-risk/poor-risk and ITT patients that were maintained through 42 months' minimum follow-up. A complete response rate >10% was achieved with NIVO+IPI regardless of risk category, with no new safety signals detected in either arm. These results support NIVO+IPI as a first-line treatment option with the potential for durable response. Trial registration number: NCT02231749 .